Digest: Untangling the influence of soft and hard selection in experimental populations—from environment to genomics*. (19th July 2018) - Jiménez‐Mena, Belén; Henriques, Romina
Abstract: Gallet et al. (2018) studied the effect of two selection regimes on the maintenance of polymorphism in experimental populations. They took two strains of Escherichia coli, each resistant to a different antibiotic, evolved them in culture conditions representing "soft" or "hard" selective regimes, and measured polymorphism levels for three to five transfers. Their results supported theoretical predictions that only "soft" selection maintains polymorphism, highlighting the importance of experimental studies to understand maintenance of variation in nature.